The modern nickel-titanium endodontic instruments using in the educational process at the department of dentistry of the Omsk State Medical Academy (Эндодонтия Today)
The students are to be good not only in the theoretical knowledge but also have good manual and analytical skills to solve various problems in practice according to the modern endodontics. The dentistry department staff of the Omsk State Medical Academy has accepted an invitation to cooperation with the company FKG Dentaire S.A. in order to support the students’ knowledge and skills in working with the root canals. The result is the acquisition of endodontic skills by the graduate and postgraduate students in working with rotary NiTi files of RaCe. When teaching students to work with rotary NiTi files, emphasis was made on quantitative control of using a too used in the root canals. FKG offers an extremely simple and yet reliable method of accounting of the use of tools SMD (Safety Memo Disk).